2016
DOI: 10.1007/s00114-016-1393-9
|View full text |Cite
|
Sign up to set email alerts
|

Weather-dependent microhabitat use by Tetrix tenuicornis (Orthoptera: Tetrigidae)

Abstract: For ectothermic animals, selection of a suitable microhabitat is affected by a combination of abiotic and biotic factors. Also important is the trade-off between those microhabitats with optimal microclimatic conditions and food availability vs. those with the lowest level of competition and lowest risk of predation. Central European species of groundhoppers (Orthoptera: Tetrigidae) live in locations with small-scale mosaics of patches formed by bare ground, moss cushions and vascular plants (grasses and forbs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Nonetheless, comparing our findings to other ecological studies of pygmy grasshoppers also revealed that association with the environment can be different among Southeast Asian species and with counterparts from other regions. For example, Tetrix undulata was shown to associate with habitats with preferred thermal properties (Ahnesjö and Forsman 2006) whereas Tetrix tenuicornis had differing preferences for microhabitats in accordance to changes in the weather conditions (Musiolek and Kočárek 2016). On the other hand, a riverine species, Tetrix ceperoi, prefers hotter, damper and bare areas, similar to species from NSSF (Gröning et al 2007).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nonetheless, comparing our findings to other ecological studies of pygmy grasshoppers also revealed that association with the environment can be different among Southeast Asian species and with counterparts from other regions. For example, Tetrix undulata was shown to associate with habitats with preferred thermal properties (Ahnesjö and Forsman 2006) whereas Tetrix tenuicornis had differing preferences for microhabitats in accordance to changes in the weather conditions (Musiolek and Kočárek 2016). On the other hand, a riverine species, Tetrix ceperoi, prefers hotter, damper and bare areas, similar to species from NSSF (Gröning et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Quantitative studies on the habitat/microhabitat association of pygmy grasshoppers are rare and restricted to a few species (e.g. Hochkirch et al 2000, Gröning et al 2007, Kuřavová and Kočárek 2015, Musiolek and Kočárek 2016, and even fewer in Southeast Asia. Southeast Asia consists of three biodiversity hotspots (Myers et al 2000), and is threatened by large-scale deforestation and land use conversion (Brooks et al 2002, Sodhi et al 2010, Wilcove et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In sum, treetops represent a refuge for locusts from nocturnal ground‐hunting predators, and when declining temperatures prevent flight escape. Many ectotherms seek refuge from predators under similar cold conditions (Cooper, ; Musiolek and Kočárek, ; Peckarsky, ; Putman & Clark, ; Rand, ). Thus, roosting in large plants during cold periods seems to be adaptive for chilled locusts and other ectotherms to counter the negative effects of decreased temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Such kinetic defences may be ineffective or impossible at low temperatures (Angilletta, Niewiarowski, & Navas, ; Christian & Tracy, ; Herrel, James, & Van Damme, ; Thomas & Blanford, ). As a result, ectotherms often use different defences at low temperatures, such as hiding, to protect themselves from predators (Cooper, ; Musiolek and Kočárek ; Peckarsky, ; Putman & Clark, ). Choosing appropriate microhabitats during periods of extreme environmental temperatures allows ectothermic prey to reduce predation (Hildrew & Townsend, ; Sih, ; Werner, Gilliam, Hall, & Mittelbach, ; Ydenberg & Dill, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation